Abacavir/lamivudine fixed dose combination in the treatment of patients with HIV infection. Issue 1 (January 2009) - Anderson, Albert ML; Lennox, Jeffrey L
HIV infection remains a common cause of morbidity and mortality worldwide. Fortunately, patients treated with combination antiretroviral therapy (ART) have significantly improved survival rates and quality of life. The standard of care for the treatment of ART-naive patients includes three drugs, two of which should be nucleoside reverse transcriptase inhibitors (NRTIs). Abacavir/lamivudine (ABC/3TC) is a fixed dose combination NRTI tablet that has been approved as an NRTI backbone. ABC/3TC is among the NRTI combinations that are recommended as first line in the most recent International AIDS Society––USA guidelines and WHO European Region protocol. However, owing to recently published data raising the possibility of an association between abacavir and heart disease, as well as data regarding efficacy in patients with higher HIV RNA levels, ABC/3TC has now been listed as an alternative NRTI backbone in the latest USA Department of Health and Human Services guidelines. While ABC has been associated with a hypersensitivity reaction that may be severe, a new test has been demonstrated to be effective in screening for the gene that is associated with this reaction.